Twenty short pieces for piano: sports et divertissements - Satie, Erik. 1866-1925 (Dover Publications, 1982)
This Dover facsimile reproduces the origial color drawings in black and white, with one color illustration on the cover, and English translations of Satie´s eccentric verbal notations.